The importance of a nutrient-rich, fertile amaranth plant salad - Khurramov Ulugbek Kholmamatovich; Bolikulov Farkhod Olimovich (International Journal on Orange Technologies, 2020)
There are a lot of unique medicinal plants in our country and one of them is the amaranth. There is no one who does not know that the plant amaranth. However, many people do not know its unique healing properties that protect human body.